Non industrial desktop publishing systems - Šarlauskienė, Lina (Information & Media, 1996)
Purpose, consistence and functions of desktop publishing systems are investigating in this article. Also features of editing and lay-out of publications there are presenting.Analysis of the equipment for desktop publishing has been done according to the cycle (input, lay-out, output) and fields (professional, industrial, personnel) of publishing. A review of most popular in publishing PC and Macintosh systems and program software for them (text and illustration editing, vector drawings, lay-out) is presenting in this article. Detail analysis has been done for technical editing and lay-outing of publications. Requirements of traditional book publishing have been taken into account.
Keywords: -